Direct synthesis of 4-hydroxycoumarins and 4-hydroxy-6-methyl-2-pyrone containing chroman-4-ones via a silver catalyzed radical cascade cyclization reaction. (6th August 2021) - Sharma, Suraj; Sarma, Bipul; Baishya, Gakul
Abstract : A novel AgNO3 /K2 S2 O8 catalyzed radical cascade cyclization reaction of 2-(allyloxy)arylaldehydes with 4-hydroxycoumarins and 4-hydroxy-6-methyl-2-pyrone produces two new series of chroman-2-ones. Abstract : For the first time, we report a novel silver catalyzed radical cascade cyclization reaction of 2-(allyloxy)arylaldehydes to synthesize two new libraries of chroman-4-ones by using 4-hydroxycoumarins and 4-hydroxy-6-methyl-2-pyrone as radical precursors. AgNO3 /K2 S2 O8 acts as an efficient oxidizing system and smoothly drives the reaction producing the 4-hydroxycoumarins and 4-hydroxy-6-methyl-2-pyrone containing chroman-4-ones in moderate to good yields. The protocol also makes different chemoselective products while using 2-(but-3-en-1-yloxy)benzaldehydes as radical acceptors. We have confirmed the participation of radicals by performing various radical trapping experiments with 2, 2, 6, 6-tetramethylpiperidine-1-oxyl, butylated hydroxytoluene, and diphenyl ethylene.